Tawjih Repitisi Lafaz Hamdalah Pada Fawatih Al-Suwar Menurut Pandangan Ibn Asyur Dalam Al-Tahrīr Wa Al-Tanwīr - Muhammad Hakim Abdul Malek; Abd Muhaimin Ahmad; Muhammad Arif Musa; Mohd Nor Adzha Ibrahim (Academic Inspired Network, 2026)
Tier 3